2019
DOI: 10.1177/2374373519893199
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Postoperative Complications From the Perspective of the Patient

Abstract: Background: Although provider-derived surgical complication severity grading systems exist, little is known about the patient perspective. Objective: To assess patient-rated complication severity and determine concordance with existing grading systems. Methods: A survey asked general surgery patients to rate the severity of 21 hypothetical postoperative events representing grades 1 to 5 complications from the Accordion Severity Grading System. Concordance with the Accordion scale was examined. Separately, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The degree of pain, and particularly dyspareunia that can impact a woman's sexual quality of life, emerged as a strong determinant for classifying the severity of the complication. This confirms the work by Rendell et al who assessed the concordance between patient perception and a complication scale, and found that the level of pain was a determining factor of patient perception of complication severity [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The degree of pain, and particularly dyspareunia that can impact a woman's sexual quality of life, emerged as a strong determinant for classifying the severity of the complication. This confirms the work by Rendell et al who assessed the concordance between patient perception and a complication scale, and found that the level of pain was a determining factor of patient perception of complication severity [12].…”
Section: Discussionsupporting
confidence: 90%
“…Slankamenac et al investigated perceptions of postoperative general surgery complications and showed that patients' and physicians' responses differed significantly [16]. More recently, Rendell et al showed that patient-rated complication severity was discordant with provider-derived grading systems, and suggested the need to explore differences between patient and provider perspectives following surgery [12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HCPs should realize that postoperative adverse events affect every patient differently, and that the impact of complications as experienced by patients does not necessarily match the clinical grading of complications severity. Minor complications, which are often not mentioned before surgery, might affect a patient's experience equally or more severely than major complications 36 . This highlights the importance of continuing patient expectation management during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…These are less significant and likely less memorable, perhaps explaining poor self-reflection. However, Rendell et al 32 report that patients may rate some minor complications as more morbid than their grade suggests. Lack of insight into quantity or quality of complications may result in surgeons not recognizing areas of deficiency in their practice.…”
Section: Discussionmentioning
confidence: 99%